IMPROVING SEMEN QUALITY OF PERANAKAN ONGOLE CATTLE WITH MARIGOLD®-BASED ANTIOXIDANT IN TRIS-EGG YOLK DILUENT - Hasan Anwar Hanafi; Abdullah Baharun; Tulus Maulana; Annisa Rahmi; Muhammad Gunawan; Athhar Manabi Diansyah (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
This study aimed to determine the optimal concentration of Marigold® antioxidant suplemented in a Tris-egg yolk (TEY) extender to maintain the quality of liquid semen from Peranakan Ongole (PO) bulls. Semen samples were extended in TEY without antioxidant (P0, control) or supplemented with Marigold® extract at concentrations of 0.002% (P1), 0.004% (P2), and 0.006% (P3). Semen quality was evaluated based on macroscopic characteristics (volume, colour, pH, and consistency) and microscopic parameters (mass motility, progressive motility, viability, plasma membrane integrity (PMI), and morphological abnormalities). Fresh semen exhibited an average volume of 5.25±0.8 mL, creamy colour, pH 6.8±0.13, mass motility (++), abnormalities 4.1±0.8%, viability 86.12±6.2%, PMI 77.21±5.3%, and progressive motility 85.44±2.41%. Supplementation with Marigold® antioxidant significantly influenced microscopic parameters during storage at 4 °C. Sperm abnormalities increased with storage duration, particularly in P3 on day 2. Treatment with 0.004% Marigold® (P2) effectively maintained motility and PMI up to day 6, while 0.006% (P3) preserved viability and PMI up to day 10. The addition of Marigold® extract to the TEY extender improved the preservation of PO bull semen quality during 10 days of storage at 4 °C. A concentration of 0.004% was optimal for maintaining sperm quality in the short term (up to day 6), whereas 0.006% provided stronger protective effects during prolonged storage (up to day 10).